Transition from nomadic pastoralism to livestock based agro-pastoralism : the case of animal husbandry in West Pokot, Kenya - Grönvall, Antonia (SLU/Dept. of Animal Nutrition and Management (until 231231), 2015)
West Pokot County is located in North Western part of Kenya where the previous lifestyle was nomadic pastoralism. However, in recent years the semi-arid county has been under dramatic developments and a sedentary agro-pastoral lifestyle is now growing. This is a major change in production systems and there is a big knowledge gap especially for the livestock based agro-pastoral systems. The main objective of this study was to investigate the current situation of animal husbandry in West Pokot. Twenty farmers were interviewed in Chepareria Division, using semi-structured interviews to investigate if the use of enclosures have had any effect on animal husbandry in West Pokot and if so, how have this method affected the animal husbandry? The results of the study indicated that there is a difference in animal husbandry between farms using enclosures and farms not using enclosures. There was a significant positive association between number of years with enclosures and total number of animals (p<0.05). Those farmers that had been using enclosures more than 12 years had considerable more animals compared to the other categories of farmers. There was a negative correlation between the use of enclosures and the use of migration (p<0.01). Only one of the farms using enclosures also migrated with the animals, while four of the five farms not using enclosures migrated. To be able to draw further conclusions about these differences, more detailed research needs to be done of the animal production in West Pokot County. The focus should be on pasture management and the supply of water and feed to animals.